El aula invertida en el área de ciencias naturales para la atención a la diversidad en el 8vo año de educación general básica - Andrade Saltos, Freddy Fabián (2021)
The inverted classroom in the area of natural sciences for the attention to diversity in the 8th year of Basic General education, this research arises from observing a deficient use of technological tools, as a means to teach classes that cover the diversity of the students, and thus obtaining the general objectives that education promotes. Theoretical content regarding the use of the flipped classroom at an international level and its use to cover the existing diversity was compiled and analyzed. Surveys, interviews and observations were carried out with the teachers of natural sciences, authorities and students of the site where the research was carried out, it was possible to evidence a low use of technological tools in the teaching process, the use of old methodologies that do not They go hand in hand with the current generation Z, their new interests and student desires for new forms of more dynamic classes to be implemented with the use of technology………….